Pancreas-related complications following gastrectomy - Wong, Joyce (Laparoscopic Surgery, 2018)
Although gastric cancer is relatively uncommon in the United States and Europe, it is a prevalent malignancy in Asia, particularly Japan and South Korea (1). Throughout surgery, minimally invasive techniques (MIS), including laparoscopic and robotic platforms, have gained popularity for their benefit in shorter post-operative patient recovery. While this is true in surgery for benign disease, minimally invasive surgery has not yet proven to be superior to open surgery for cancer. Increasing data from multiple centers, however, continues to show non-inferiority of the MIS approach.